EFL Teachers’ Attitudes Towards a Glocalized Approach: An International, Mixed-Methods Study - Bin-Hady, Wagdi; Sarnou, Hanane; Schug, Daniel (Masyarakat Linguistik Indonesia Universitas Andalas, 2024)
Glocalization is the practice of combining global and local approaches. In English language teaching, it involves adapting materials to reflect the students’ local environment while still equipping them with intercultural communication skills. Nevertheless, it is a phenomenon that teachers are unfamiliar with in many parts of the world. Guided by glocalization research, this study aims to study the teaching practices of university instructors of English as a foreign language (EFL) in Yemen, Algeria, and France, as well as their attitudes towards glocalization. A mixed-methods approach was adopted, including both a questionnaire addressed to 78 teachers and interviews with a select group of 21 EFL professors and instructors working in the three countries, to understand and analyze their use of a glocalized approach for teaching EFL. The results revealed that EFL teachers in all three countries recognized the importance of applying a glocalized approach in their classrooms and used a variety of strategies, technologies, and materials to implement it. Finally, the study found no significant differences in the attitudes of EFL teachers in Yemen, Algeria, and France towards adopting glocalized approaches. Still, some noticeable differences can be observed, particularly in how teachers in the different countries glocalized their classrooms. French participants, for example, focused on the types of documents studied in class and how they were selected, while the Algerian and Yemeni participants focused their comments on their general strategies. This study highlights the awareness of EFL teachers of the importance of including local values while teaching a foreign language to their students.